Analisis Strategi Pemasaran pada Hotel Toraja Prince di Kecamatan Tallunglipu Kabupaten Toraja Utara di Masa Pandemi Covid-19 - Rical Rical; Adriana Madya Marampa; Stefani Marina Palimbong (Universitas Veteran Bangun Nusantara, 2022)
This study aims to find out what strategy is appropriate or in accordance with the Toraja Prince Hotel during the Covid 19 Pandemic. This study uses a qualitative method, namely a case study that produces descriptive data that is poured into words. By using SWOT, Matrix, EFAS, and IFAS research techniques and cartecius diagrams. Data collection techniques in this study the authors made a direct visit to the Toraja Prince Hotel to conduct a personal interview with the President Director, Mr. Francoise Tomasoa. Therefore Conclusion Based on the company's internal and external analysis along with the Cartesian diagram, it can be concluded that Toraja Prince Hotel is in Quadrant I, namely Supporting Aggressive Strategy (positive-positive) which indicates Toraja Prince Hotel is in a strong position and has the opportunity to make it possible to carry out activities to increase growth and development. Based on the results of the SWOT Matrix, alternative strategies are obtained, namely SO, WO, ST, and WT strategies.